ANALYSIS OF VERBAL HUMOR IN JIMMY O.YANG’S STAND-UP COMEDY SPECIAL GUESS HOW MUCH - Nur Hikmah; Auliyanti Sahril Nurfadhilah; Nur Mutmainna (Journal of English Literature and Linguistic Studies, 2026)
This study aims to analyze of verbal humor in Jimmy O. Yang's stand-up comedy special Guess How Much using Shade's theory of verbal humor classification and the General Theory of Verbal Humor (GTVH) by Raskin and Attardo. Shade categorizes verbal humor into twelve types: pun, riddle, joke, satire, limerick, parody, anecdote, farce, irony, sarcasm, tall tale, and wit. Meanwhile, GTVH identifies six interrelated knowledge resources used to construct humor: Script Opposition (SO), Logical Mechanism (LM), Situation (SI), Target (TA), Narrative Strategy (NS), and Language (LA). This research uses a qualitative descriptive method, with data collected from the transcript of the performance video, focusing on utterances that contain verbal humor. The results show that 11 out of 12 types of verbal humor appear in the performance, with anecdote being the most dominant, found in 15 out of 61 humorous utterances. This reflects Jimmy O. Yang's storytelling-based comedic style, which relies heavily on personal experiences, cultural background, and everyday life. Based on the types of humor found, the results also indicate that all six Knowledge Resources from GTVH are used in constructing the verbal humor.This study reveals that Jimmy O. Yang's humor is not only entertaining but also reflects his identity as an Asian-American and his experience growing up in an immigrant family. The combination of Shade's theory and GTVH provides a comprehensive understanding of how verbal humor is structured and meaningful. The findings show that verbal humor in stand-up comedy can serve as a vehicle for cultural expression, identity construction, and social commentary, while also engaging the audience through powerful and personal storytelling.